Secondary battery and electronic device

By setting active material layers with different conductivity on the electrode assembly of the lithium-ion battery, the problem of black spots and lithium separation on the outer electrode plates of the electrode assembly is solved, and the circulation and safety performance are improved.

CN119170855AActive Publication Date: 2024-12-20NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202411216709.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-31
Publication Date
2024-12-20
Estimated Expiration
2044-08-31

AI Technical Summary

Technical Problem

The outer electrode plates of the electrode assembly in lithium-ion batteries are prone to black spots or lithium extraction, resulting in a decrease in circulation performance and a decrease in safety performance.

Method used

By providing different active material layers on the single-side outer first electrode sheet and the inner first electrode sheet of the electrode assembly, the conductivity is regulated, so that the conductivity of the single-side outer electrode sheet is less than or equal to the conductivity of the inner electrode sheet, and the current is reduced Density, slows down electrolyte consumption, reduces the risk of black spots and lithium excretion.

Benefits of technology

It effectively reduces the risk of black spots and lithium excretion on the outer electrode plate of the electrode assembly, and improves the circulation and safety performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170855A_ABST
    Figure CN119170855A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device, and the secondary battery comprises an electrode assembly which comprises a first pole piece, a second pole piece and a diaphragm. The first pole pieces comprise two outer side first pole pieces and an inner side first pole piece, and the two outer side first pole pieces are located on the two outermost sides of the electrode assembly respectively. The first pole piece comprises a first current collector and a first active material layer; the first current collector comprises a first surface and a second surface; at least one outer side first pole piece is a single-face first pole piece, and the first active substance layer arranged on the second surface of the single-face first pole piece is a first material layer. First active substance layers are arranged on the first surface and the second surface of the inner side first pole piece, and the first active substance layers arranged on the first surface and the second surface of the inner side first pole piece are second material layers. The conductivity of the single-side first pole piece is a S / cm, the conductivity of the inner-side first pole piece is b S / cm, and a is smaller than or equal to b. Through the arrangement, the risks of black spots and lithium precipitation of the pole piece on the outer side of the electrode assembly are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries, such as lithium-ion batteries, have the characteristics of large specific energy, high operating voltage, low self-discharge rate, small size and light weight, and are widely used in the field of consumer electronics.

[0003] At present, the electrode assembly in lithium-ion batteries often adopts a multi-electrode and laminated structure to reduce the battery impedance. Among them, in order to ensure the ultra-thin and high energy density performance of lithium-ion batteries, the outermost pole piece of the electrode assembly usually adopts a single-sided coated pole piece. However, due to the manufacturing process and structural particularity of the single-sided coated pole piece, black spots or lithium precipitation are prone to occur during the cycle, resulting in reduced performance of lithium-ion batteries. Summary of the invention

[0004] The purpose of the present application is to provide a secondary battery and an electronic device to reduce the risk of black spots and lithium deposition on the outer pole pieces of the electrode assembly and to improve the cycle performance of the secondary battery.

[0005] It should be noted that in the invention content of the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0006] In order to reduce process costs and increase the energy density of secondary batteries in the prior art, the outermost pole piece of the electrode assembly of the multi-pole stacking structure in the lithium-ion battery is usually a single-sided coated pole piece, that is, a material layer is set only on one side of the current collector of the pole piece, and the inner pole piece is usually a double-sided coated pole piece, and the material layers of the inner and outer pole pieces generally have the same ratio of various substances, which will make the outer current density of the electrode assembly significantly higher than the inner current density. During the secondary battery cycle, the electrolyte consumption rate on the outer side of the electrode assembly is faster, and black spots or lithium deposition are prone to occur on the outer single-sided coated pole piece, resulting in a decrease in the cycle performance of the secondary battery and a decrease in safety performance. Based on this, the present application provides a secondary battery that can reduce the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly and improve the cycle performance of the secondary battery. The specific technical solution is as follows:

[0007] The first aspect of the present application provides a secondary battery, including a shell and an electrode assembly of a laminate structure, along the thickness direction of the electrode assembly, the electrode assembly includes a first pole piece, a second pole piece and a diaphragm arranged between the first pole piece and the second pole piece; the electrode assembly also includes a first pole lug assembly and a second pole lug assembly, the first pole lug assembly includes a plurality of first pole lugs, the second pole lug assembly includes a plurality of second pole lugs, the plurality of first pole lugs correspond to the first pole piece one by one, and the plurality of second pole lugs correspond to the second pole piece one by one. The first pole piece includes two outer first pole pieces and at least one inner first pole piece, along the thickness direction of the electrode assembly, the two outer first pole pieces are respectively located on the outermost sides of the electrode assembly, and the inner first pole piece is located between the two outer first pole pieces. The first pole piece includes a first current collector and a first active material layer, the first current collector includes a first surface and a second surface arranged opposite to each other along the thickness direction of the electrode assembly, and the first surface is closer to the shell than the second surface. At least one outer first pole piece is a single-sided first pole piece, and the first active material layer is not provided on the first surface of the single-sided first pole piece, and the first active material layer is provided on the second surface of the single-sided first pole piece, and the first active material layer provided on the second surface of the single-sided first pole piece is a first material layer. The first active material layer is provided on both the first surface and the second surface of the inner first pole piece, and the first active material layer provided on the first surface and the second surface of the inner first pole piece is a second material layer. The conductivity of the single-sided first pole piece is a S / cm, and the conductivity of the inner first pole piece is b S / cm, a≤b. By providing different first active material layers on the single-sided outer first pole piece and the inner first pole piece of the electrode assembly, and making the conductivity of the single-sided outer first pole piece less than or equal to the conductivity of the inner first pole piece, the current density of the outer pole piece of the electrode assembly is reduced, the consumption rate of the electrolyte during the cycle is reduced, and the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is reduced, thereby improving the cycle performance of the secondary battery.

[0008] In one embodiment of the present application, 0.3≤a / b≤1. In one embodiment of the present application, 0.65≤a / b≤1. By adjusting the value of a / b within the above range, it is helpful to reduce the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0009] In one embodiment of the present application, the first pole piece is a positive pole piece, which has a more obvious effect of reducing the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle, thereby further improving the cycle performance of the secondary battery.

[0010] In one embodiment of the present application, the first material layer includes a first binder, and the mass percentage of the first binder is c based on the mass of the first material layer; the second material layer includes a second binder, and the mass percentage of the second binder is d based on the mass of the second material layer, and 0.6≤c / d≤4. By regulating the value of c / d within the above range, the impedance of the outer electrode sheet of the electrode assembly is increased compared with the outer electrode sheet of the conventional electrode assembly, thereby slowing down the consumption rate of the electrolyte on the outer side of the electrode assembly during the cycle, which is beneficial to reduce the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0011] In one embodiment of the present application, 2%≤c≤5%; the first binder and the second binder are each independently selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polyvinylidene chloride, aramid, polyamide, polyacrylonitrile, acrylate polymer, styrene-butadiene rubber, polyacrylate, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, pure acrylic emulsion or polyacrylic acid. By selecting the first binder and the second binder within the above-mentioned range, and regulating the mass percentage of the first binder within the above-mentioned range, it is helpful to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0012] In one embodiment of the present application, the first material layer includes a first conductive agent, the second material layer includes a second conductive agent, and the first conductive agent and the second conductive agent are each independently selected from at least one of conductive carbon black, carbon nanotubes, graphene or conductive graphite. Based on the mass of the first material layer, the mass percentage of the first conductive agent is 0.5% to 5%, and based on the mass of the second material layer, the mass percentage of the second conductive agent is 1% to 10%. By selecting the first conductive agent and the second conductive agent within the above-mentioned range, and regulating the mass percentage of the first conductive agent and the mass percentage of the second conductive agent within the above-mentioned range, it is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0013] In one embodiment of the present application, the first material layer includes a first active material, the second material layer includes a second active material, and the first active material and the second active material are each independently selected from at least one of lithium cobalt oxide, lithium iron phosphate, lithium nickel oxide, lithium manganese oxide, nickel cobalt manganese ternary material or lithium-rich manganese-based material. Based on the mass of the first material layer, the mass percentage of the first active material is 90% to 97.5%, and based on the mass of the second material layer, the mass percentage of the second active material is 87% to 98.5%. By selecting the first active material and the second active material within the above-mentioned range, and regulating the mass percentage of the first active material and the mass percentage of the second active material within the above-mentioned range, it is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0014] In one embodiment of the present application, 0.01≤b≤0.8. By regulating the conductivity of the inner first pole piece within the above range, the current density of the inner pole piece of the electrode assembly during the cycle is relatively large, which is beneficial to improving the cycle performance of the secondary battery.

[0015] In one embodiment of the present application, the thickness of the first current collector of the single-sided first pole sheet is T1μm, and the thickness of the first current collector of the inner first pole sheet is T2μm, and T1≥T2. In one embodiment of the present application, the first pole sheet is a positive pole sheet, 12≤T1≤25, 6≤T2≤16. In one embodiment of the present application, the first pole sheet is a negative pole sheet, 14≤T1≤25, 4≤T2≤16. The above-mentioned arrangement is conducive to improving the problem of warping caused by uneven stress of the first current collector due to only one surface material layer being arranged on the first current collector of the single-sided first pole sheet. At this time, a double-layer material layer is arranged on the outer single-sided first pole sheet of the electrode assembly, and the conductivity of the single-sided first pole sheet is made less than or equal to the conductivity of the inner first pole sheet. The effect of reducing the risk of black spots and lithium deposition on the outer pole sheet of the electrode assembly during the cycle is more obvious, and the secondary battery has good cycle performance.

[0016] In one embodiment of the present application, the shell is an aluminum-plastic film. When the aluminum-plastic film is selected as the shell, it is beneficial to reduce the risk of short circuit of the secondary battery and improve the cycle performance and safety performance of the secondary battery.

[0017] In one embodiment of the present application, the secondary battery further includes an electrolyte, the electrolyte includes a lithium salt, the lithium salt includes at least one of lithium tetrafluorophosphate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium bis(fluorosulfonyl)imide or lithium difluorophosphate, and the concentration of the lithium salt is 1 mol / L to 5 mol / L. When a lithium salt within the above-mentioned range is selected and the concentration of the lithium salt is regulated within the above-mentioned range, the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is reduced, and the secondary battery has a high energy density and good cycle performance.

[0018] In one embodiment of the present application, the first pole piece is a negative pole piece, 0.5≤a / b≤1, 0.1≤b≤10. When the first pole piece is a negative pole piece, different first active material layers are arranged on the first pole piece on the outer side and the first pole piece on the inner side of the single-sided electrode assembly, and the values ​​of a / b and b are regulated within the above range, which is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0019] In one embodiment of the present application, the shell is a steel shell. When a steel shell is selected as the shell, it is beneficial to reduce the risk of short circuit of the secondary battery, enhance the hardness of the secondary battery, and improve the cycle performance and safety performance of the secondary battery.

[0020] The second aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. The secondary battery of the present application has good cycle performance, so the electronic device of the present application has a long service life.

[0021] Beneficial effects of the embodiments of the present application:

[0022] The present application provides a secondary battery and an electronic device, which adjusts the conductivity of the first outer electrode sheet on a single side to be less than or equal to the conductivity of the first inner electrode sheet. At this time, the current density at the outermost side of the electrode assembly is reduced, and the consumption rate of the electrolyte during the cycle is slowed down, which can effectively reduce the risk of black spots and lithium deposition on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0023] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0025] Figure 1 A schematic diagram of a cross-sectional structure of a secondary battery according to an embodiment of the present application observed along its length direction;

[0026] Figure 2 for Figure 1 Another schematic cross-sectional structure diagram of a secondary battery observed along its length direction.

[0027] Figure numerals: secondary battery 001; electrode assembly 01; shell 02; first pole piece 10; outer first pole piece 101; inner first pole piece 102; first current collector 11; first active material layer 12; first material layer 121; second material layer 122; second pole piece 20; second current collector 21; second active material layer 22; first pole tab assembly 13; first pole tab 131; second pole tab assembly 23; second pole tab 231; diaphragm 30. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0029] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0030] The first aspect of the present application provides a secondary battery, including a shell and an electrode assembly of a laminate structure, along the thickness direction of the electrode assembly, the electrode assembly includes a first pole piece, a second pole piece and a diaphragm arranged between the first pole piece and the second pole piece; the electrode assembly also includes a first pole lug assembly and a second pole lug assembly, the first pole lug assembly includes a plurality of first pole lugs, the second pole lug assembly includes a plurality of second pole lugs, the plurality of first pole lugs correspond to the first pole piece one by one, and the plurality of second pole lugs correspond to the second pole piece one by one. The first pole piece includes two outer first pole pieces and at least one inner first pole piece, along the thickness direction of the electrode assembly, the two outer first pole pieces are respectively located on the outermost sides of the electrode assembly, and the inner first pole piece is located between the two outer first pole pieces. The first pole piece includes a first current collector and a first active material layer, the first current collector includes a first surface and a second surface arranged opposite to each other along the thickness direction of the electrode assembly, and the first surface is closer to the shell than the second surface. At least one outer first pole piece is a single-sided first pole piece, the first surface of the single-sided first pole piece is not provided with a first active material layer, the second surface of the single-sided first pole piece is provided with a first active material layer, and the first active material layer provided on the second surface of the single-sided first pole piece is a first material layer. The first active material layer is provided on both the first surface and the second surface of the inner first pole piece, and the first active material layer provided on the first surface and the second surface of the inner first pole piece is a second material layer. The electrical conductivity of the single-sided first pole piece is a S / cm, and the electrical conductivity of the inner first pole piece is b S / cm, where a≤b.

[0031] In this application, the electrode assembly of the laminated structure is defined as having a width direction of X, a length direction of Y, and a thickness direction of Z. It is understood that the length direction, width direction, and thickness direction of the first electrode sheet, the second electrode sheet, and the diaphragm are the same as those of the electrode assembly. For example, Figure 1 and Figure 2As shown, the secondary battery 001 includes an electrode assembly 01 and a shell 02 of a laminated structure. Along the thickness direction Z direction of the electrode assembly 01, the electrode assembly 01 includes a first pole piece 10 and a second pole piece 20 stacked and a diaphragm 30 arranged between the first pole piece 10 and the second pole piece 20; the electrode assembly 01 also includes a first pole ear assembly 13 and a second pole ear assembly 23. The first pole ear assembly 13 includes a plurality of first pole ears 131, and the second pole ear assembly 23 includes a plurality of second pole ears 231. The plurality of first pole ears 131 correspond to the first pole piece 10 one by one, and the plurality of second pole ears 231 correspond to the second pole piece 20 one by one. The first pole piece 10 includes two outer first pole pieces 101 and an inner first pole piece 102. Along the thickness direction Z direction of the electrode assembly 01, the two outer first pole pieces 101 are respectively located on the outermost sides of the electrode assembly 01, and the inner first pole piece 102 is located between the two outer first pole pieces 101. The first pole piece 10 includes a first current collector 11 and a first active material layer 12. The first current collector 11 includes a first surface (not shown in the figure) and a second surface (not shown in the figure) arranged opposite to each other along the thickness direction Z direction of the electrode assembly 01. The first surface is closer to the housing 02 than the second surface. The two outer first pole pieces 101 are single-sided first pole pieces. The first active material layer 12 is not arranged on the first surface of the single-sided first pole piece. The first active material layer 12 is arranged on the second surface of the single-sided first pole piece. The first active material layer 12 arranged on the second surface of the single-sided first pole piece is a first material layer 121. The first active material layer 12 is arranged on both the first surface and the second surface of the inner first pole piece 102. The first active material layer 12 arranged on the first surface and the second surface of the inner first pole piece 102 is a second material layer 122.

[0032] The inventors have found that by coating different first active material layers on the first pole piece on the outer side and the first pole piece on the inner side of the electrode assembly, the conductivity of the first pole piece on the outer side of the electrode assembly is greater than or equal to the conductivity of the first pole piece on the inner side, that is, A≤B, and the current density of the outer pole piece of the electrode assembly is reduced, which slows down the consumption rate of the electrolyte in the outer pole piece of the electrode assembly during the cycle, thereby reducing the risk of black spots and lithium deposition in the outer pole piece of the electrode assembly, and improving the cycle performance of the secondary battery. When the current density of the outermost layer of the electrode assembly is greater than the current density of the inner layer, that is, A>B, the electrolyte in the outer pole piece of the electrode assembly is consumed too quickly, and black spots or lithium deposition problems are likely to occur in the outer pole piece of the electrode assembly, reducing the cycle performance and safety performance of the secondary battery. Therefore, by arranging different first active material layers on the single-sided outer first pole sheet and the inner first pole sheet of the electrode assembly, and making the electrical conductivity of the single-sided outer first pole sheet less than or equal to the electrical conductivity of the inner first pole sheet, the current density of the outer pole sheet of the electrode assembly is reduced, thereby reducing the consumption rate of the electrolyte during the cycle, reducing the risk of black spots and lithium deposition on the outer pole sheet of the electrode assembly during the cycle, and improving the cycle performance of the secondary battery.

[0033] It should be noted that the first active material layer of the present application can be provided on the entire surface area of ​​the first current collector or on a partial surface area of ​​the first current collector. The present application has no particular limitation as long as the purpose of the present application can be achieved.

[0034] In one embodiment of the present application, 0.3≤a / b≤1. For example, the value of a / b can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or a range consisting of any two of these values. By regulating the value of a / b within the above range, the current density of the outer electrode sheet of the electrode assembly is greater than or equal to the current density of the inner electrode sheet, and the consumption rate of the electrolyte during the cycle is slowed down, which is conducive to reducing the risk of black spots and lithium deposition on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0035] In one embodiment of the present application, 0.65≤a / b≤1. For example, the value of A / B can be 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1 or a range consisting of any two of these values. By regulating the value of a / b within the above range, the current density of the outer pole piece of the electrode assembly is greater than or equal to the current density of the inner pole piece, and the consumption rate of the electrolyte during the cycle is slowed down, which is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0036] In one embodiment of the present application, the first pole piece is a positive pole piece. When the positive pole piece is selected as the first pole piece, the first pole piece on the outside of the electrode assembly is the positive pole piece, which further slows down the consumption rate of the electrolyte on the outside of the electrode assembly during the cycle, and has a more obvious effect of reducing the risk of black spots and lithium deposition on the pole piece on the outside of the electrode assembly during the cycle, thereby further improving the cycle performance of the secondary battery.

[0037] In one embodiment of the present application, the first material layer includes a first binder, and the mass percentage of the first binder is c based on the mass of the first material layer; the second material layer includes a second binder, and the mass percentage of the second binder is d based on the mass of the second material layer, and 0.6≤c / d≤4. For example, the value of c / d can be 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4 or a range consisting of any two values ​​therein. By regulating the value of c / d within the above range, the impedance of the outer electrode sheet of the electrode assembly is increased compared with the outer electrode sheet of the conventional electrode assembly, and the content of the first binder and the second binder are used in combination, while reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, and reducing the polarization during the conversion of the active material, which is beneficial to reduce the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0038] In one embodiment of the present application, 2%≤c≤5%; for example, the value of c can be 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or a range consisting of any two of the values. The first binder and the second binder are each independently selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polyvinylidene chloride, aramid, polyamide, polyacrylonitrile, acrylate polymer, styrene-butadiene rubber, polyacrylic acid salt, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, pure acrylic emulsion or polyacrylic acid. By selecting the first binder and the second binder within the above-mentioned range and adjusting the mass percentage of the first binder within the above-mentioned range, it is beneficial to increase the impedance of the outer electrode sheet of the electrode assembly and reduce the conductivity of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly and slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, which is beneficial to reduce the risk of black spots and lithium deposition on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0039] In one embodiment of the present application, the first material layer includes a first conductive agent, and the second material layer includes a second conductive agent, and the first conductive agent and the second conductive agent are each independently selected from at least one of conductive carbon black, carbon nanotubes, graphene or conductive graphite. Based on the mass of the first material layer, the mass percentage content W1 of the first conductive agent is 0.5% to 5%. For example, the mass percentage content W1 of the first conductive agent can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or a range consisting of any two of the values. Based on the mass of the second material layer, the mass percentage content W2 of the second conductive agent is 1% to 10%. For example, the mass percentage content W2 of the second conductive agent can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or a range consisting of any two values ​​therein. By selecting the first conductive agent and the second conductive agent within the above-mentioned range, and regulating the mass percentage content of the first conductive agent and the mass percentage content of the second conductive agent within the above-mentioned range, the first conductive agent and the second conductive agent are used in combination, which is conducive to increasing the impedance of the outer electrode sheet of the electrode assembly and reducing the conductivity of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, and reducing the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0040] In one embodiment of the present application, the first material layer includes a first active material, and the second material layer includes a second active material. The first active material and the second active material are each independently selected from at least one of lithium cobalt oxide, lithium iron phosphate, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material or lithium-rich manganese-based material. Based on the mass of the first material layer, the mass percentage content W'1 of the first active material is 90% to 97.5%. For example, the mass percentage content W'1 of the first active material can be 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5% or a range consisting of any two of the values; based on the mass of the second material layer, the mass percentage content W'1 of the second active material is .... The percentage content W'2 is 87% to 98.5%. For example, the mass percentage content W'2 of the second active material can be 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5% or a range consisting of any two of the values. The first active material and the second active material are selected within the above-mentioned range, and the mass percentage of the first active material and the mass percentage of the second active material are adjusted within the above-mentioned range. The first active material and the second active material are used together to increase the impedance of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte on the outer side of the electrode assembly during the cycle, and helping to reduce the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery. In this application, nickel-cobalt-manganese ternary materials include but are not limited to LiNi 0.90 Co 0.05 Mn 0.05 At least one of NCM955, NCM811, NCM622, NCM523 or NCM111. The lithium-rich manganese-based material is a composite positive electrode material Li2MnO3·LiMO2 based on Li2MnO3, wherein M is a binary or ternary layered material of Ni, Co, Mn or Ni, Co, Mn.

[0041] In one embodiment of the present application, 0.01≤b≤0.8. For example, the value of b can be 0.01, 0.012, 0.015, 0.018, 0.02, 0.05, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or a range consisting of any two of these values. By regulating the conductivity of the inner first pole piece within the above range, the current density of the outer pole piece of the electrode assembly during the cycle is small, which is beneficial to improving the cycle performance of the secondary battery.

[0042] In one embodiment of the present application, the thickness of the first current collector of the single-sided first pole piece is T1 μm, the thickness of the first current collector of the inner first pole piece is T2 μm, and T1 ≥ T2. In one embodiment of the present application, the first pole piece is a positive pole piece, 12 ≤ T1 ≤ 25, 6 ≤ T2 ≤ 16; for example, the value of T1 can be 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 or a range consisting of any two of the values, and the value of T2 can be 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or a range consisting of any two of the values. In one embodiment of the present application, the first pole piece is a negative pole piece, 14≤T1≤25, 4≤T2≤16; for example, the value of T1 can be 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 or a range consisting of any two of the values, and the value of T2 can be 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or a range consisting of any two of the values. Through the above arrangement, it is beneficial to improve the problem of warping caused by uneven stress of the first current collector caused by only one surface material layer on the first current collector of the single-sided first pole piece. At this time, a double-layer material layer is arranged on the outer single-sided first pole piece of the electrode assembly, and the conductivity of the single-sided first pole piece is made less than or equal to the conductivity of the inner first pole piece. The effect of reducing the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is more obvious, and the secondary battery has good cycle performance.

[0043] In one embodiment of the present application, the shell is an aluminum-plastic film. When the aluminum-plastic film is used as the shell and the first pole piece on the outer side of the electrode assembly is used as the positive pole piece, it is beneficial to reduce the risk of short circuit of the secondary battery and improve the cycle performance and safety performance of the secondary battery.

[0044] In one embodiment of the present application, the secondary battery further comprises an electrolyte, the electrolyte comprises a lithium salt, the lithium salt comprises at least one of lithium tetrafluorophosphate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalate)borate, lithium bis(fluorosulfonyl)imide or lithium difluorophosphate, and the concentration ω of the lithium salt is 1 mol / L to 5 mol / L. For example, the concentration ω of the lithium salt may be 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, 2.5 mol / L, 2.8 mol / L, 3 mol / L, 3.2 mol / L, 3.5 mol / L, 3.8 mol / L, 4 mol / L, 4.2 mol / L, 4.5 mol / L, 4.8 mol / L, 5 mol / L or a range consisting of any two of the values. By selecting lithium salts within the above-mentioned range and regulating the concentration of lithium salts within the above-mentioned range, it is beneficial to the transmission of ions in the electrolyte. When used in combination with the binder in the first active material layer, it is beneficial to form a stable interface with good interface consistency, reducing the conductivity of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, and helping to reduce the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0045] In the present application, when the first electrode sheet or the second electrode sheet is a positive electrode sheet, the present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0046] In one embodiment of the present application, the first pole piece is a negative pole piece, 0.5≤a / b≤1, 0.1≤b≤10. For example, the value of a / b can be 0.5, 0.6, 0.7, 0.8, 0.9, 1 or a range consisting of any two of the values; the value of b can be 0.1, 0.3, 0.5, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range consisting of any two of the values. When the first pole piece is a negative pole piece, different first active material layers are coated on the first pole piece on the outer side of the single-sided electrode assembly and the first pole piece on the inner side, and the values ​​of a / b and b are adjusted within the above range. Compared with the outer pole piece of the conventional electrode assembly, the impedance of the outer pole piece of the electrode assembly is increased, thereby reducing the current density of the outer pole piece of the electrode assembly, slowing down the consumption rate of the electrolyte on the outer side of the electrode assembly during the cycle, which is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0047] In one embodiment of the present application, the shell is a steel shell. When the steel shell is selected as the shell and the first pole piece on the outer side of the electrode assembly is used as the negative pole piece, it is beneficial to reduce the risk of short circuit of the secondary battery and improve the cycle performance and safety performance of the secondary battery.

[0048] In one embodiment of the present application, the first electrode sheet is a negative electrode sheet, and the first binder and the second binder are independently selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polyvinylidene chloride, aramid, polyamide, polyacrylonitrile, acrylate polymer, styrene-butadiene rubber, polyacrylate, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, pure acrylic emulsion or polyacrylic acid, and the mass percentage of the first binder is 0.5% to 5% based on the mass of the first material layer, and the mass percentage of the second binder is 0.5% to 5% based on the mass of the second material layer. When the first electrode sheet is a negative electrode sheet, the first binder and the second binder are selected within the above-mentioned range, and the mass percentage of the first binder and the mass percentage of the second binder are regulated within the above-mentioned range. The first binder and the second binder are used together to increase the impedance of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, which is conducive to reducing the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0049] In one embodiment of the present application, the first electrode sheet is a negative electrode sheet, and the first conductive agent and the second conductive agent are independently selected from at least one of conductive carbon black, conductive graphite, carbon fiber (VGCF), carbon nanotube (CNT) or graphene. Based on the mass of the first material layer, the mass percentage of the first conductive agent is 0.5% to 10%, and based on the mass of the second material layer, the mass percentage of the second conductive agent is 0.5% to 10%. When the first electrode sheet is a negative electrode sheet, the first conductive agent and the second conductive agent are selected within the above-mentioned type range, and the mass percentage of the first conductive agent and the mass percentage of the second conductive agent are regulated within the above-mentioned range. The first conductive agent and the second conductive agent are used in combination, which increases the impedance of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, and is conducive to reducing the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0050] In one embodiment of the present application, the first pole piece is a negative pole piece, and the first active material and the second active material are independently selected from at least one of natural graphite, artificial graphite, soft carbon, hard carbon, activated carbon, lithium-alloy, lithium-titanium alloy, lithium-silicon dioxide, lithium-phosphorus oxide, lithium-sulfide, silicon-based material, titanate material or boron nitride material. Based on the mass of the first material layer, the mass percentage of the first active material is 90% to 99%, and based on the mass of the second material layer, the mass percentage of the second active material is 90% to 99%. When the first pole piece is a negative pole piece, the first active material and the second active material are selected within the above-mentioned range, and the mass percentage of the first active material and the mass percentage of the second active material are regulated within the above-mentioned range. The first active material and the second active material are used in combination, which increases the impedance of the outer pole piece of the electrode assembly, thereby reducing the current density of the outer pole piece of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, and is conducive to reducing the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0051] In the present application, when the first pole piece or the second pole piece is a negative pole piece, the present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector (such as lithium copper composite current collector, carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.).

[0052] The present application has no particular restrictions on the preparation method of the outer first pole piece, as long as the purpose of the present application can be achieved. For example, the preparation method of the outer first pole piece includes but is not limited to the following steps: (1) mixing the first active material, the first binder and the first conductive agent in a certain mass ratio and adding a solvent to prepare a first material layer slurry; (2) coating the first material layer slurry on one surface of the first current collector, and after drying, obtaining a single-sided outer first pole piece coated with the first material layer; (3) repeating the above steps on the other surface of the first current collector to obtain a double-sided outer first pole piece coated with the first material layer; (4) cold pressing, cutting and welding the first pole ear to obtain the outer first pole piece.

[0053] In the present application, the conductivity of the outer first pole piece can be regulated by regulating the mass percentage of the first binder, the mass percentage of the first conductive agent and the mass percentage of the first active material. For example, when other conditions are constant, the mass percentage of the first active material remains unchanged, the mass percentage of the first binder increases, the mass percentage of the corresponding first conductive agent decreases, and the conductivity of the outer first pole piece decreases; the mass percentage of the first binder decreases, the mass percentage of the corresponding first conductive agent increases, and the conductivity of the outer first pole piece increases. In the present application, the mass percentage of the first active material, the first binder and the first conductive agent can be regulated by regulating the mass ratio of the first active material, the first binder and the first conductive agent. In the present application, the conductivity of the outer first pole piece is also related to the overall thickness of the outer first pole piece, the coating weight of the corresponding material layer, etc. For example, for the outer first pole piece of the same specification, when other conditions are the same, the outer first pole piece has a smaller thickness and a smaller coating weight, and the conductivity of the outer first pole piece is larger. The present application has no particular restrictions on the solvent and solid content of the first material layer slurry in the above step (1), as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the temperature and time of drying in the above step (2), and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the process parameters of cold pressing, cutting and welding the first pole ear in the above step (4), and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the size of the above-mentioned first material layer, as long as the purpose of the present application can be achieved.

[0054] The present application has no particular restrictions on the preparation method of the inner first pole piece, as long as the purpose of the present application can be achieved. For example, the preparation method of the inner first pole piece includes but is not limited to the following steps: (1) mixing the second active material, the second binder and the second conductive agent in a certain mass ratio and adding a solvent to prepare a second material layer slurry; (2) coating the second material layer slurry on one surface of the first current collector, and drying to obtain a single-sided inner first pole piece coated with the second material layer; (3) repeating the above steps on the other surface of the first current collector to obtain a double-sided inner first pole piece coated with the second material layer; (4) cold pressing, cutting and welding the first pole ear to obtain the inner first pole piece.

[0055] In the present application, the conductivity of the inner first pole piece can be regulated by regulating the mass percentage of the second binder, the mass percentage of the second conductive agent and the mass percentage of the second active material. For example, when other conditions are constant, the mass percentage of the second active material remains unchanged, the mass percentage of the second binder increases, the mass percentage of the corresponding second conductive agent decreases, and the conductivity of the inner first pole piece decreases; the mass percentage of the second binder decreases, the mass percentage of the corresponding second conductive agent increases, and the conductivity of the inner first pole piece increases. In the present application, the mass percentage of the second active material, the second binder and the second conductive agent can be regulated by regulating the mass ratio of the second active material, the second binder and the second conductive agent. In the present application, the conductivity of the inner first pole piece is also related to the overall thickness of the inner first pole piece, the coating weight of the corresponding material layer, etc. For example, for the inner first pole piece of the same specification, when other conditions are the same, the thickness of the inner first pole piece is smaller and the coating weight is less, the conductivity of the inner first pole piece is larger. The present application has no particular restrictions on the solvent and solid content of the second material layer slurry in the above step (1), as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the temperature and time of drying in the above step (2), and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the process parameters of cold pressing, cutting and welding the first pole ear in the above step (4), and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the size of the above second material layer, as long as the purpose of the present application can be achieved.

[0056] In one embodiment of the present application, the electrolyte further includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethyl propylene (EA) or methyl propionate (MA). When an organic solvent within the above-mentioned range is selected and used in combination with a lithium salt, it is beneficial to reduce the conductivity of the outer pole piece of the electrode assembly, thereby reducing the current density of the outer pole piece of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, and helping to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.

[0057] The electrolyte of the present application also includes other solvents. The present application has no particular restrictions on other solvents, as long as the purpose of the present application can be achieved. For example, other solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorocarbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dipropyl carbonate, methyl propyl carbonate or ethyl propyl carbonate. The above-mentioned cyclic carbonate may include but are not limited to at least one of butylene carbonate or vinyl ethylene carbonate. The fluorinated carbonate compound may include, but is not limited to, at least one of fluorinated ethylene carbonate, 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.

[0058] The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or at least one of aramid. The type of diaphragm may include at least one of woven membranes, non-woven membranes, microporous membranes, composite membranes, rolled membranes or spun membranes. The diaphragm of the present application may have a porous structure, and the present application has no particular restrictions on the size of the pore size of the porous structure of the diaphragm, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01 μm to 1 μm. The present application has no particular restrictions on the thickness of the diaphragm, as long as the purpose of the present application can be achieved. For example, the thickness of the diaphragm can be 5 μm to 40 μm.

[0059] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one or more embodiments, the secondary battery may include, but is not limited to, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0060] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no special limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the outer first pole piece, diaphragm, second pole piece, diaphragm, inner first pole piece, diaphragm, second pole piece, diaphragm, and outer first pole piece in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of the stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0061] The second aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. The secondary battery of the present application has good cycle performance, so the electronic device of the present application has a long service life.

[0062] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0063] Example

[0064] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0065] Test methods and equipment:

[0066] Conductivity test of the electrode:

[0067] The lithium-ion battery discharged at 0.2C to 3.0V was disassembled, and the outer first pole piece of the electrode assembly was taken out. According to the arrangement of the pole pieces in the electrode assembly, the inner first pole piece of the electrode assembly was taken out, and soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. Then, the outer first pole piece and the inner first pole piece were placed in an oven and baked at 80°C for 12 hours to obtain the treated outer first pole piece and inner first pole piece samples.

[0068] Use a resistivity tester (IEST, BER1200, Yuanneng Technology) to test the first outer electrode and the first inner electrode after treatment. Before use, reset the resistance and pressure of the resistance tester, place the electrode sample to be tested between the electrodes of the tester, take three different positions of the electrode with a cross-sectional area of ​​30mm×30mm on the sample for testing, and measure the resistance values ​​of three electrode pieces with a cross-sectional area of ​​30mm×30mm. Take the average value and record it as the resistance value of the electrode with a cross-sectional area of ​​30mm×30mm and record it as the resistance value of the electrode piece to be tested. And calculate according to the following formula:

[0069] R=ρ×l / s; γ=1 / ρ=l / Rs

[0070] Where R is the measured resistance value; ρ is the resistivity; l is the thickness of the measured electrode, s is the cross-sectional area, and γ is the measured conductivity of the electrode.

[0071] The conductivity a of the outer first pole piece and the conductivity b of the inner first pole piece are obtained respectively.

[0072] Lithium salt concentration test in electrolyte:

[0073] The lithium-ion battery is discharged to 3V at 0.2C and then disassembled, the electrolyte is collected, and the disassembled first electrode piece, second electrode piece, and diaphragm are centrifuged, and the liquid obtained after centrifugation and the above electrolyte are mixed evenly to obtain a liquid sample. The liquid sample is subjected to ion chromatography (IC) test to measure the concentration of lithium salt in the electrolyte.

[0074] Lithium deposition performance test:

[0075] The lithium-ion battery in the embodiment and the comparative example is placed in a thermostat at 10°C. After 60 minutes, it is charged to 4.5V at 2C constant current, charged to 0.05C at 4.5V constant voltage, and left to stand for 5 minutes. Then, it is discharged to 3.0V at 0.5C constant current. This is one cycle. After 100 cycles of the above charge and discharge process, it is charged to 4.5V at 2C constant current, charged to 0.05C at 4.5V constant voltage, and left to stand for 5 minutes. After that, the lithium-ion battery is disassembled, the outer pole piece of the electrode assembly is taken out, and the lithium deposition state on the surface of the outer pole piece is observed. The non-lithium deposition area on the outer pole piece surface is golden yellow, and the lithium deposition area is grayish white.

[0076] The criteria for judging the degree of lithium deposition in lithium-ion batteries are as follows: a lithium deposition area of ​​0% means no lithium deposition, i.e., the degree of lithium deposition is zero; a lithium deposition area greater than 0 and less than or equal to 2% means mild lithium deposition, i.e., the degree of lithium deposition is mild; a lithium deposition area greater than 2% and less than or equal to 20% means moderate lithium deposition, i.e., the degree of lithium deposition is moderate; a lithium deposition area greater than 20% and less than or equal to 100% means severe lithium deposition, i.e., the degree of lithium deposition is severe, wherein the percentage of the lithium deposition area is calculated based on the total area of ​​the first active material layer of the outer first electrode.

[0077] Black spot test:

[0078] Place the lithium-ion battery in a 0℃ constant temperature box and let it stand for 60 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at 0℃ with a constant current of 1C to a full charge voltage of 4.5V, then charge it to 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, and then discharge it to 3.0V at a constant current of 1C; this is a charge and discharge cycle. After 500 cycles of charge and discharge, charge it to a full charge voltage of 4.5V at a constant current of 1C, and then charge it to 0.025C at a constant voltage of 4.5V to obtain a fully charged battery with 500 cycles. Disassemble the lithium-ion battery in a dry room with a humidity of less than 5%, and take photos to record whether there are black spots on the surface of the outer pole piece.

[0079] The criteria for judging the degree of black spots in lithium-ion batteries are as follows: a black spot area of ​​0% means no black spots appear, a black spot area less than or equal to 2% means mild black spots, a black spot area of ​​2% to 20% means moderate black spots, and a black spot area greater than 20% means severe black spots, where the percentage of the black spot area is calculated based on the total area of ​​the first active material layer of the outer first pole piece.

[0080] Cycle performance test:

[0081] Place the lithium-ion battery in a 25℃ constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25℃. Charge to 4.5V at 1C constant current, charge to 0.025C at 4.5V constant voltage, let stand for 5 minutes, and discharge to 3.0V at 0.2C constant current. This is the first cycle, and the initial discharge capacity is recorded as C0. Perform charge and discharge cycles on the lithium-ion battery according to the above process. When the cycle reaches 400 cycles (cls), stop the test and record the discharge capacity after 400 cycles (cls) as C1. Calculate the 400cls capacity retention rate as an indicator for evaluating the cycle performance of lithium-ion batteries.

[0082] 400cls capacity retention rate (%) = C1 / C0×100%.

[0083] The higher the 400cls capacity retention rate, the better the cycle performance of the lithium-ion battery.

[0084] Example 1

[0085] <Preparation of the first pole piece>

[0086] A positive electrode plate is selected as the first plate, and the first active material lithium cobalt oxide, the first binder polyvinylidene fluoride, and the first conductive agent conductive carbon black are mixed in a mass ratio of 96.5:3:0.5, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a first material layer slurry with a solid content of 70wt%. The first material layer slurry is coated on one surface of a positive electrode current collector aluminum foil with a thickness of 14μm. After baking at 120°C for 1 hour, a positive electrode plate coated with the first material layer on one side is obtained, that is, a single-sided outer positive electrode plate. After cold pressing, cutting, and welding the positive electrode ears, an outer positive electrode plate with a specification of 50mm×90mm is obtained. Among them, the coating weight of the first material layer is 16mg / mm 2 The thickness of the first material layer is 50 μm. Based on the mass of the first material layer, the mass percentage c of the first binder is 3%, the mass percentage W1 of the first conductive agent is 0.5%, and the mass percentage W'1 of the first active material is 96.5%.

[0087] The second active material lithium cobalt oxide, the second binder polyvinylidene fluoride, and the second conductive agent conductive carbon black are mixed in a mass ratio of 97.5:1.5:1 and added with N-methylpyrrolidone (NMP), and stirred evenly under the action of a vacuum mixer to obtain a second material layer slurry with a solid content of 70wt%. The second material layer slurry is coated on one surface of a positive electrode collector aluminum foil with a thickness of 14μm, and baked at 120°C for 1 hour to obtain a positive electrode sheet coated with a second material layer on one side. Repeat the above steps on the other surface of the positive electrode collector aluminum foil to obtain a positive electrode sheet coated with a second material layer on both sides. Then, after drying under vacuum conditions at 120°C for 1 hour, the inner positive electrode sheet with a specification of 50mm×90mm is obtained by cold pressing, cutting, and welding the positive electrode ears. Among them, the coating weight of the second material layer is 16mg / mm 2 The thickness of the double-sided second material layer is 100 μm. Based on the mass of the second material layer, the mass percentage d of the second binder is 1.5%, the mass percentage W2 of the second conductive agent is 1%, and the mass percentage W'2 of the second active material is 97.5%.

[0088] <Preparation of the Second Pole Sheet>

[0089] A negative electrode sheet was selected as the second electrode sheet, and the negative electrode active material artificial graphite, conductive carbon black, and negative electrode binder styrene-butadiene rubber were mixed in a mass ratio of 94:2:4, deionized water was added, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 65wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and baked at 120°C for 1 hour to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The above steps were repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided coating of a negative electrode material layer. After drying under vacuum conditions at 120°C for 1 hour, a negative electrode sheet with a specification of 50mm×90mm was obtained by cold pressing, cutting, and welding the negative electrode ears. Among them, the coating weight of the negative electrode material layer is 11mg / mm 2 The thickness of the double-sided negative electrode material layer is 110μm.

[0090] <Preparation of Electrolyte>

[0091] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed at a mass ratio of 1:1:1 to obtain an organic solvent; lithium salt lithium hexafluorophosphate (LiPF6) is dissolved in the organic solvent and mixed evenly to obtain an electrolyte. The concentration of lithium salt LiPF6 is 3 mol / L.

[0092] <Diaphragm>

[0093] A polyethylene (PE) film with a thickness of 7 μm was used as the separator.

[0094] <Preparation of lithium-ion batteries>

[0095] The outer positive electrode sheet, separator, negative electrode sheet, separator, inner positive electrode sheet, separator, negative electrode sheet, separator, and outer positive electrode sheet prepared above are stacked in order, and then the four corners of the entire stacked structure are fixed with tape to obtain an electrode assembly of the stacked structure, and the electrode assembly is placed in an aluminum plastic film, placed in an 80°C vacuum oven for 12 hours to remove moisture, and the prepared electrolyte is injected, and a lithium-ion battery is obtained after vacuum packaging, standing, formation, degassing, trimming and other processes. The design potential range of the lithium-ion battery is 3.0V to 4.5V.

[0096] Example 2 to Example 18

[0097] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1. When the concentration of lithium salt in the electrolyte changes, the concentration of the organic solvent changes accordingly, and the mass ratio of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) remains unchanged.

[0098] Embodiment 19

[0099] Except for preparing the first pole piece, the second pole piece and the lithium-ion battery according to the following steps and adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0100] <Preparation of the first pole piece>

[0101] A negative electrode plate is selected as the first plate, and the first active material artificial graphite, the first binder styrene-butadiene rubber (SBR), and the first conductive agent carbon nanotube (CNT) are mixed in a mass ratio of 96.5:3:0.5 and added with deionized water, and stirred evenly under the action of a vacuum mixer to obtain a first material layer slurry with a solid content of 65wt%. The first material layer slurry is coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm. After baking at 120°C for 1 hour, a negative electrode plate coated with the first material layer on one side is obtained, that is, a single-sided outer negative electrode plate. After cold pressing, cutting, and welding the negative electrode ears, an outer negative electrode plate with a specification of 50mm×90mm is obtained. Among them, the coating weight of the first material layer is 12mg / mm 2 The thickness of the first material layer is 60 μm. Based on the mass of the first material layer, the mass percentage c of the first binder is 3%, the mass percentage W1 of the first conductive agent is 0.5%, and the mass percentage W′1 of the first active material is 96.5%.

[0102] The second active material artificial graphite, the second binder styrene-butadiene rubber (SBR), and the second conductive agent carbon nanotube (CNT) are mixed in a mass ratio of 96.5:1.5:2 and added to deionized water, and stirred evenly under the action of a vacuum mixer to obtain a second material layer slurry with a solid content of 65wt%. The second material layer slurry is coated on one surface of a negative electrode collector copper foil with a thickness of 12μm, and baked at 120°C for 1 hour to obtain a negative electrode sheet coated with the second material layer on one side, and the above steps are repeated on the other surface of the negative electrode collector copper foil to obtain a negative electrode sheet coated with the second material layer on both sides. Then, after drying under vacuum conditions at 120°C for 1 hour, the inner negative electrode sheet with a specification of 50mm×90mm is obtained by cold pressing, cutting, and welding the negative electrode ears. Among them, the coating weight of the second material layer is 12mg / mm 2 The thickness of the double-sided second material layer is 120 μm. Based on the mass of the second material layer, the mass percentage d of the second binder is 1.5%, the mass percentage W2 of the second conductive agent is 2%, and the mass percentage W'2 of the second active material is 96.5%.

[0103] <Preparation of the Second Pole Sheet>

[0104] A positive electrode sheet was selected as the second electrode sheet, and the positive electrode active material lithium cobalt oxide, the binder polyvinylidene fluoride, and the conductive agent conductive carbon black were mixed in a mass ratio of 92.5:1.5:6, and N-methylpyrrolidone (NMP) was added. The mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 14μm, and baked at 120°C for 1 hour to obtain a positive electrode sheet with a single-sided positive electrode material layer. The above steps were repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. After drying under vacuum conditions at 120°C for 1 hour, a positive electrode sheet with a specification of 60mm×90mm was obtained by cold pressing, cutting, and welding the positive electrode ears. Among them, the coating weight of the positive electrode material layer is 18mg / mm 2 The thickness of the double-sided positive electrode material layer is 108μm.

[0105] <Preparation of lithium-ion batteries>

[0106] The outer negative electrode sheet, separator, positive electrode sheet, separator, inner negative electrode sheet, separator, positive electrode sheet, separator, and outer negative electrode sheet prepared above are stacked in order, and then the four corners of the entire stacked structure are fixed with tape to obtain an electrode assembly of the stacked structure, and the electrode assembly is placed in a steel shell, placed in an 80°C vacuum oven for 12 hours to remove moisture, and the prepared electrolyte is injected, and a lithium-ion battery is obtained after vacuum packaging, standing, formation, degassing, trimming and other processes. The design potential range of the lithium-ion battery is 3.0V to 4.5V.

[0107] Example 20 to Example 21

[0108] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 19.

[0109] Comparative Example 1 to Comparative Example 3

[0110] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0111] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1 and Table 2.

[0112]

[0113]

[0114] Table 2

[0115]

[0116] It can be seen from Examples 1 to 21 and Comparative Examples 1 to 3 that by adjusting the conductivity of the single-sided first pole piece to be less than or equal to the conductivity of the inner first pole piece, the black spot area of ​​the outer pole piece of the electrode assembly is smaller, the lithium precipitation area is smaller, and the 400cls capacity retention rate of the lithium-ion battery is improved, indicating that the lithium-ion battery of the present application can reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, and the lithium-ion battery has good cycle performance. The various parameters of the first material layer and the second material layer in Comparative Example 1 are exactly opposite to the various parameters of the first material layer and the second material layer in Example 1; the conductivity of the single-sided first pole piece in Comparative Examples 1 to 3 is greater than the conductivity of the inner first pole piece; the black spot area of ​​the lithium-ion battery in Comparative Examples 1 to 3 is larger; the lithium precipitation area is larger, and the 400cls capacity retention rate is lower. In the lithium-ion batteries in Examples 1 to 21, the black spot area and lithium deposition area of ​​the outer first pole piece are relatively small, and the 400cls capacity retention rate is relatively high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is relatively low, and the lithium-ion batteries have good cycle performance.

[0117] The c / d value usually affects the cycle performance of lithium-ion batteries. It can be seen from Examples 1 to 3 that when the c / d value is adjusted within the scope of this application, the black spot area and lithium deposition area of ​​the first outer pole piece in the lithium-ion battery are small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.

[0118] The type and content of the first binder, and the type and content of the second binder usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1 to 14 that when the first binder and the second binder within the scope of this application are selected, and the content of the first binder and the content of the second binder are adjusted within the scope of this application, the black spot area and lithium precipitation area of ​​the first pole piece on the outside of the lithium-ion battery are small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.

[0119] The type and content of the first conductive agent, and the type and content of the second conductive agent usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1 to 14 that when the first conductive agent and the second conductive agent within the scope of the present application are selected, and the content of the first conductive agent and the second conductive agent are adjusted within the scope of the present application, the black spot area and lithium precipitation area of ​​the first pole piece on the outside of the lithium-ion battery are small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.

[0120] The type and content of the first active material and the type and content of the second active material usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1 to 14 that when the first active material and the second active material within the scope of this application are selected, and the content of the first active material and the content of the second active material are regulated within the scope of this application, the black spot area and lithium precipitation area of ​​the first pole piece on the outside of the lithium-ion battery are small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.

[0121] The conductivity b of the inner first pole piece usually affects the cycle performance of the lithium-ion battery. It can be seen from Examples 1 to 18 that when the value of b is adjusted within the scope of this application, the black spot area and lithium precipitation area of ​​the outer first pole piece in the lithium-ion battery are small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.

[0122] The type and concentration of lithium salts usually affect the cycle performance of lithium-ion batteries. It can be seen from Examples 6 and 15 to 18 that when lithium salts within the scope of this application are selected and the concentration of the lithium salts is adjusted within the scope of this application, the black spot area and lithium precipitation area of ​​the first pole piece on the outside of the lithium-ion battery are small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.

[0123] The type of the first pole piece usually affects the cycle performance of the lithium-ion battery. It can be seen from Example 1 and Example 19 that when the first pole piece is a positive pole piece or a negative pole piece, the black spot area and lithium deposition area of ​​the outer first pole piece in the lithium-ion battery are small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.

[0124] When the first pole piece is a negative pole piece, the value of a / b and the value of b usually affect the cycle performance of the lithium-ion battery. From Example 19 to Example 21, it can be seen that by regulating the value of a / b and the value of b within the scope of the present application, the black spot area and lithium precipitation area of ​​the outer first pole piece in the lithium-ion battery are small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.

[0125] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0126] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0127] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A secondary battery, comprising a housing and an electrode assembly of a laminate structure, wherein along the thickness direction of the electrode assembly, the electrode assembly comprises a first electrode sheet, a second electrode sheet and a diaphragm arranged between the first electrode sheet and the second electrode sheet; the electrode assembly further comprises a first pole tab assembly and a second pole tab assembly, the first pole tab assembly comprises a plurality of first pole tabs, the second pole tab assembly comprises a plurality of second pole tabs, the plurality of first pole tabs correspond to the first pole sheet one by one, and the plurality of second pole tabs correspond to the second pole sheet one by one; The first pole piece includes two outer first pole pieces and at least one inner first pole piece, and along the thickness direction of the electrode assembly, the two outer first pole pieces are respectively located at the outermost two sides of the electrode assembly, and the inner first pole piece is located between the two outer first pole pieces; The first electrode sheet includes a first current collector and a first active material layer, the first current collector includes a first surface and a second surface arranged opposite to each other along the thickness direction of the electrode assembly, and the first surface is closer to the housing than the second surface; At least one of the outer first pole pieces is a single-sided first pole piece, the first surface of the single-sided first pole piece is not provided with the first active material layer, the second surface of the single-sided first pole piece is provided with the first active material layer, and the first active material layer provided on the second surface of the single-sided first pole piece is a first material layer; The first active material layer is provided on the first surface and the second surface of the inner first pole piece, and the first active material layer provided on the first surface and the second surface of the inner first pole piece is a second material layer; The electrical conductivity of the single-sided first pole piece is a S / cm, and the electrical conductivity of the inner first pole piece is b S / cm, where a≤b.

2. The secondary battery according to claim 1, wherein 0.3≤a / b≤1.

3. The secondary battery according to claim 2, wherein: 0.65≤a / b≤1.

4. The secondary battery according to any one of claims 1 to 3, wherein The first pole piece is a positive pole piece.

5. The secondary battery according to claim 4, wherein The first material layer includes a first adhesive, and based on the mass of the first material layer, the mass percentage of the first adhesive is c; the second material layer includes a second adhesive, and based on the mass of the second material layer, the mass percentage of the second adhesive is d, 0.6≤c / d≤4.

6. The secondary battery according to claim 5, wherein 2%≤c≤5%; the first binder and the second binder are each independently selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polyvinylidene chloride, aramid, polyamide, polyacrylonitrile, acrylate polymer, styrene-butadiene rubber, polyacrylic acid salt, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, pure acrylic emulsion or polyacrylic acid.

7. The secondary battery according to claim 4, wherein The first material layer includes a first conductive agent, and the second material layer includes a second conductive agent, and the first conductive agent and the second conductive agent are each independently selected from at least one of conductive carbon black, carbon nanotubes, graphene or conductive graphite; based on the mass of the first material layer, the mass percentage of the first conductive agent is 0.5% to 5%, and based on the mass of the second material layer, the mass percentage of the second conductive agent is 1% to 10%.

8. The secondary battery according to claim 4, wherein The first material layer includes a first active material, and the second material layer includes a second active material, and the first active material and the second active material are each independently selected from at least one of lithium cobalt oxide, lithium iron phosphate, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material or lithium-rich manganese-based material; based on the mass of the first material layer, the mass percentage of the first active material is 90% to 97.5%, and based on the mass of the second material layer, the mass percentage of the second active material is 87% to 98.5%.

9. The secondary battery according to claim 4, wherein 0.01≤b≤0.8。 10. The secondary battery according to claim 1 or 2, wherein: The thickness of the first current collector of the single-sided first pole piece is T1 μm, the thickness of the first current collector of the inner first pole piece is T2 μm, and T1 ≥ T2.

11. The secondary battery according to claim 10, wherein The first pole piece is a positive pole piece, 12≤T1≤25, 6≤T2≤16.

12. The secondary battery according to claim 10, wherein The first pole piece is a negative pole piece, 14≤T1≤25, 4≤T2≤16.

13. The secondary battery according to claim 4, wherein The shell is an aluminum-plastic film.

14. The secondary battery according to claim 5, wherein The secondary battery also includes an electrolyte, the electrolyte includes a lithium salt, the lithium salt includes at least one of lithium tetrafluorophosphate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium bis(fluorosulfonyl)imide or lithium difluorophosphate, and the concentration of the lithium salt is 1 mol / L to 5 mol / L.

15. The secondary battery according to claim 1 or 2, wherein: The first pole piece is a negative pole piece, 0.5≤a / b≤1, 0.1≤b≤10.

16. The secondary battery according to claim 12, wherein The shell is a steel shell. 17 . An electronic device comprising the secondary battery according to claim 1 .

Citation Information

Patent Citations

  • An electrochemical device and an electronic device comprising the same

    CN109244475A

  • Positive pole piece, secondary battery and electric device

    CN115986130A

  • Secondary battery and electric device

    CN117203800A

  • Secondary battery and electronic device

    CN117728043A

  • Electrochemical device and electronic device

    WO2024164769A1

Cited By

  • Secondary battery and electronic device

    WO2026045631A1

  • Secondary battery and electric device

    WO2026165796A1